ARABIC-AN ATTEMPT TO CORRECT THE CREDENTIALS ERRORS OCCURRED IN AL-MU'JAM AL-AWSAT WRITTEN BY IMAM AL-TABRANI (A CRITICAL STUDY OF HADITH) - Sayyed wali Ullah shah; Masood Ahmed (دی اسکالر)
Imam Sulaiman bin Ahmad Al-Tabarani was a famous Muhaddith of 3rd and 4th century AH. He has significant services in the field of "Ilm ul Elal". His famous book in this regard is "Al-Mujam Al Awsat". He has explained the "Al-Elal" of ahadith in this book. He mentioned "Elal" are based on the differences and disagreements of the narrators. The said book is unique in this regard, however, there are errors in same places. A critical research study of its five hundred (500) ahadith has found thirty-six (36) errors in it. Most of the errors are found in the credentials. These include errors in narrator's names, their father names, and errors in the credentials. These errors are mentioned in the article. Arguments has been given regarding these errors. This research invites a critical research study of this book in this regard, so that it can be corrected.